Down-regulation of Rous sarcoma virus long terminal repeat promoter activity by a HeLa cell basic protein. - Yeh, C H (1994)
We have previously isolated a HeLa cell cDNA encoding a 21-kDa polypeptide that is 48% similar to transcription factor IIS. To explore the possibility that p21 plays a role in transcriptional regulation in vivo, we tested the effect of p21 expression on the synthesis of reporter chloramphenicol acetyltransferase (CAT) in transfected COS-1 cells. CAT formation under control of the Rous sarcoma virus long terminal repeat (RSV LTR) promoter was decreased nearly 20-fold in cells coexpressing p21. In contrast, CAT production under control of other sequence elements was only slightly reduced (human immunodeficiency virus type 1 LTR, simian virus 40 early promoter), unaffected (human heat shock protein of 70-kDa promoter, adenovirus major late promoter TATA box), or increased (terminal deoxynucleotidyltransferase initiator element, c-fos promoter) by p21 coexpression as compared to cells cotransfected with the parental vector. The abundance of steady-state CAT transcripts from RSV LTR was also decreased by p21 expression in a dose-dependent manner, suggesting that transcription of RSV LTR/CAT is under negative control by p21. Consistent with an effect on transcription, p21 was localized in nuclei of transfected cells. Deletion analysis of p21 indicated that the sequences essential for inhibition of RSV LTR function include the previously identified ARg/Ser-rich region and zinc finger-like motif. Proliferation of chicken embryo fibroblasts transfected with an infectious molecular clone of RSV was diminished by p21 expression, which also resulted in fewer transformed foci.